Cost-effectiveness of thrombolytics: a simplified model - RABUŞ, ŞULE (SPRINGER, 2005)
Objective of the study: To construct a simple model for an internal, retrospective cost-effectiveness analysis and to calculate the incremental cost-effectiveness of tissue plasminogen activator (TPA) over streptokinase (SK) in Turkey. Setting: Kosuyolu Heart, Education and Research Hospital, Istanbul, Turkey. Method: Among patients who were hospitalized for treatment of acute myocardial infarction (AMI), 196 were randomly selected. One-year mortality rates according to the treatment groups (TPA, SK, other) were determined. Among surviving patients, 28 from TPA and another 28 from SK group were randomly selected for the pharmacoeconomic analysis. Patient treatment data were taken from medical records while data regarding to costs were taken from hospital bills. Main outcome measures: Incremental cost-effectiveness ratio (ICER). The cost part of the ratio was considered as 'the overall-costs', while the effectiveness part was considered as 'lives saved' per treatment group. Results: With an increased one-year survival rate of 2.37% and an increased cost of 1120.8 pound ($1165.6) per patient in the TPA group, the ICER for the use of TPA instead of SK was 47,289 pound ($49,180.6) per life saved. Conclusion: This model can be a guide for similar analyses. The results of our study (the incremental cost-effectiveness of TPA over SK) will be informative for the decision-makers in Turkey, by whom the medical benefit for money spent would be assessed and judged. We believe that our results make a contribution to similar studies in the literature.
Keywords: incremental cost-effectiveness; pharmacoeconomic model; sensitivity analysis; streptokinase; thrombolytics; tissue plasminogen activator; Turkey; ACUTE MYOCARDIAL-INFARCTION; TISSUE-PLASMINOGEN-ACTIVATOR; STREPTOKINASE; ALTEPLASE; THERAPY